A Novel Method Based on Digital Image Processing Technique and Finite Element Method for Rapidly Modeling Optical Properties of Actual Microstructured Optical Fibers - Jianshe Li; Shuguang Li; Guanghua Gu; Hui Li; Qiang Liu; Zhenkai Fan; Hailiang Chen; Xiaoming Han; Yuanyuan Zhao; Pu Zhang (IEEE Photonics Journal)
The cross-section image of microstructure optical fiber (MOF) is usually characterized by the irregular shape, disordered distribution of the air pores, and multiple sources of noise. The traditional modeling of fiber structure does not work for these MOFs, and it is difficult to obtain the actual cross-section structure. A new method based on the digital image processing technique and finite element method (FEM) is introduced. With this method, the actual cross-section structure of MOFs can be rapidly modeled by gray scale processing, filtering, threshold, and edge detection, which is vital to the simulation of the basic properties of the fiber with FEM precisely. The method is proved to be feasible and reliable in that the dispersion coefficients of an actual fiber simulated are greatly consistent with the experimental results. In addition, the influence of perfect matched layer thinkness, as well as the curve fitting interval selection of the dispersion coefficients on the research results, is explored in the paper, which forms a basis for the correct setting of these parameters. The method has the advantages of strong adaptability, good modeling effect, rapid simulation, and accurate results. Finally, the method applies to all kinds of cross-section modeling of fiber, especially for disordered structure modeling.